2006
DOI: 10.1007/s00167-006-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament anatomy and function relating to anatomical reconstruction

Abstract: Recently, the interest in surgical techniques that reconstruct the anteromedial (AM) and the posterolateral (PL) bundles of the anterior cruciate ligament (ACL) has risen. This review focuses on the structural as well as the mechanical properties of the ACL and the anatomical details of the femoral origin, midsubstance, and tibial insertion of AM and PL bundles of the ACL. The terminology of AM and PL bundles is chosen according to the tibial insertion and determined by their functional tensioning pattern thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
231
1
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(265 citation statements)
references
References 66 publications
4
231
1
20
Order By: Relevance
“…16,17 Recently, double bundle ACL has gained in popularity where each bundle of the ACL is reconstructed separately with correct tensioning pattern of each bundle. The AM bundle is taut throughout the knee range of motion, reaching a maximum of between 458 and 608, whereas the PL bundle is tight primarily in extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Recently, double bundle ACL has gained in popularity where each bundle of the ACL is reconstructed separately with correct tensioning pattern of each bundle. The AM bundle is taut throughout the knee range of motion, reaching a maximum of between 458 and 608, whereas the PL bundle is tight primarily in extension.…”
Section: Discussionmentioning
confidence: 99%
“…The AM bundle is taut throughout the knee range of motion, reaching a maximum of between 458 and 608, whereas the PL bundle is tight primarily in extension. 16 Therefore, the AM and PL bundles are fixated accordingly, to restore their native tensioning behaviors. An in vivo kinematics study has shown that conventional singlebundle ACL reconstruction, which most closely imitates AM bundle reconstruction, can successfully restore anterior knee stability but does not sufficiently bring back rotational stability.…”
Section: Discussionmentioning
confidence: 99%
“…The functional anatomy of the normal ACL fiber bundles has drawn interest (Zantop et al, 2006;Siebold et al, 2008). Detailed knowledge of the bundle anatomy of the ACL is of great clinical value, particularly in ACL reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of ACL reconstruction is not only to obtain the knee stability without loss of motion, but also to restore the same kinematics as the native knee. Therefore, more anatomical reconstructions in which tendon grafts were placed at original attachment sites of each fiber bundle to mimic the native anatomy as closely as possible, were developed (Odensten and Gillquist, 1985;Muneta et al, 1999;Shino et al, 2005;Zantop et al, 2006;Otsubo et al, 2007;Siebold et al, 2008). Actually, the multiple bundle ACL reconstruction such as double bundle reconstruction has been increasingly popular in the clinical settings (Muneta et al, 1999;Otsubo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1 Accurate, anatomic ACL graft position re-creates the normal anatomy and improves stability, both rotational and anteroposterior stability, of a patient's knee joint. 2 Tunnel malposition is a technical error that has been shown to significantly increase the rate of graft failure and poor functional outcomes.…”
mentioning
confidence: 99%